Quantification of fat in the posterior sacroiliac joint region: fat volume is sex and age dependant - Poilliot, Amélie (Sci Rep, 2019)
Fat is appreciated as a structural component of synovial joints. It may serve a shock-absorbing function for the incongruent surfaces, vessels and ligaments, but has not been investigated in the posterior sacroiliac joint (PSIJ). Sixty-six cadaveric hemipelves were serially-sectioned and photographed. The amount of visible fat in the PSIJ was quantified using a modified version of Cavalieri’s method. Total volume, fat volume and fat percentage of the PSIJ were calculated in predefined sub-regions. Fat is consistently present in the PSIJ (1.9 ± 1.3 cm(3)). Fat volume correlates with the PSIJ total volume (p < 0.0001; r = 0.73) and age (p = 0.024; r = 0.24), and is smaller in males (1.4 ± 0.8 cm(3)) than females (2.4 ± 1.5 cm(3)). Fat volumes in the middle and inferior sub-regions of the PSIJ show side- (p < 0.0001) and sex-differences (p = 0.013 females, middle sub-region). Age and PSIJ total volume correlate between sexes in various sub-regions (p = 0.05 females superior sub-region; males inferior sub-region). Fat percentage differs between sexes and sub-regions (p = 0.018 females, superior sub-region) but is independent of age and sides. The presence of fat within the PSIJ is a normal finding and shows sex-dependant and age-related differences. It is unclear whether fat is linked to age-related degeneration or has a shock-absorbing role in stress- and load-dissipation in the PSIJ.